Do Job Stress Factors Affecting Quality of Work Life (QWL) of Bangladeshi Bank’s Employee? - NAHAR, REZBIN; ISMAIL, IZHAIRI BT.; OMAR, AZURA BT.; ISLAM, RAFIKUL (International Journal of Psychosocial Rehabilitation, 2020)
Job Stress is a rising issue faced by employers as well as employees in every modern society. This research would analyze one of the factors called Job Stress, impacting the employees 'QWL (Quality of Work Life) within the organization that is essential for the work environment and organizational competence. The primary function of this research is to establish a conceptual framework which will empirically evaluate to identify factors of Job Stress impact on QWL, as well as to determine the effect that is directly related to QWL on the conduct of individual employees. Bangladesh's banking sector is now growing and human resources are employed here, pretty much continuously suffering from workplace stress. Three variables were identified through telephone survey and related literature to classify causal variables that were directly related to job stress. This research will be carried out on the employees of the public and private banks primarily to examine the gaps between the services. The degree of Religious Coping Style has also been described as moderating variables from different literature review that may have some major effect between Job Stress and QWL connection. This current study will be determined on the basis of the information gathered from interviews and surveys. Self-administered, close-ended questionnaires would then randomly be asked to gather data from the respondents, and semi - structured questionnaire will also be undertaken among the major cities of Bangladesh by the various bank's HR manager. Descriptive Analysis, Exploratory Factor Analysis (EFA), confirmatory factor analysis (CFA), SEM (Structural Equation Model) or PLS (Partial least squares) will be conducted for data analysis using SPSS and AMOS software.